A systematic review of quality components of patients’ medical record in Iranian Hospital - Gommnami, Nasser; Juni, Muhamad Hanafiah; Md Said, Salmiah; Syed Hassan, Syed Tajuddin; Arya, Eghbali (Community Health Society Malaysia, 2015)
Background: Quality of patients’ medical records is important in patient management, safety, decision making and continuation of care. Patients’ medical record data are also used in clinical research, health system services and management, medical forensic management, quality improvement, health care financial management, and risk management. Objective: The aims of the study were to determine the quality of the components of hospital patients’ medical records. Methods: The criteria selected for systematic searching were published articles in English from 1995 to 2014 for patient medical record quality components. The search terms were hospital patient medical record, reliability, accuracy, completeness, availability and accessibility. The study was carried out from 2013 to 2014 using public domain databases which include PubMed, Cochrane and CINHAL. Results: Over 2600 citations from the databases were extracted. Based on the criteria of the study 344 articles were selected for review. Subsequently, 7 articles were selected for reliability, 11 for accuracy, 18 for completeness and 9 for availability and accessibility. These articles were subjected to an in-depth review. Reliability of data in patients’ medical record is a requisite for accuracy and completeness of clinical data. The reliability scores of the studies reviewed ranged from 49% to 99%, while accuracy of patients’ medical record ranged from 73% to 95%. The reviewed studies also showed completeness of patients’ medical record ranging from 41.5% to 93%, while availability and accessibility scores ranged from 58% to 94.3%. Conclusion: This review had contributed to a better understanding of the quality of patients’ medical record. Reliability, accuracy, completeness and accessibility of patient medical record showed a wide range of quality of patients’ medical record. Good quality of patients’ medical record is essential for patient care and through preventing medical error. This review also revealed the importance of intervention to improve quality of patient medical record.